STUDENTS’ PERCEPTION ON GOOGLE CLASSROOM ASSISTED LEARNING IN LIMITED FACE-TO-FACE INSTRUCTIONS DURING THE PANDEMIC - Novita Febrianti; Ni Nyoman Padmadewi (Language and Education Journal Undiksha, 2022)
This study aimed to identify and analyze the students’ perception toward the use of Google Classroom in English online learning. The investigation of the students’ perception becomes necessary since it can be used as a consideration for school on whether to keep using Google Classroom to facilitate face-to-face learning or not to use it at all. This research was designed using the Mixed Method research where the Descriptive Quantitative Data were dominant, while the qualitative data were used as the data supportive. Data were collected through two instruments namely a questionnaire and an interview guide. SMP N 1 Kubutambahan was chosen as the research setting and 63 students were selected as the research subjects. The results showed that the mean score of the data was 3.64. This indicated that the students of SMP N 1 Kubutambahan had a positive perception towards Google Classroom-assisted learning. Based on the interview data, the majority of students had a positive perception towards Google Classroom-assisted learning. Despite the difficulty, the majority of students wanted to continue using Goggle Classroom to assist the learning process.